(untitled) (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
The results of studies according to the strength of masonry from silicate brick compressive, depending on the thickness of the mortar joints. Determination of the deformability of masonry from silicate bricks made on samples-fours made of silicate corpulent cells connected in cement-sand mortar. Correlations obtained the mean strength of masonry in compression and deformation modulus of masonry at different values of the controlled parameter, which is the ratio of the thickness of the bricks to the thickness of the seam. It was shown that the strength of masonry in compression decreases with decreasing values of Tb/tjoint, that is, by increasing the thickness of the seam. Deformation modulus of masonry takes the maximum value at the largest and the smallest values of Tb/tjoint (samples P8 and P20) and the minimum – at the value for P15. A statistical evaluation of compressive strength of brick-fours samples at different ratios Tb/tjoint, determined that this size distribution laws subject to normal distribution defined statistical parameters: sample mean, sample standard deviation and coefficient of variation. Keywords: the brickwork, mortar joint, compression strength, deformation modulus, statistical evaluation.